马来西亚槟城潮剧的发展:从老赛永丰到潮艺馆的研究 - 张, 祖兴 (2023)
中国戏曲是渗透一代代华人社会生活的千年文化之河。以大锣鼓及 潮州管弦乐器伴奏的潮剧于 20 世纪初随着潮汕地区先民过番传播到东南 亚各国，饶富的地域性文化孕育并浇铸出独特的马来西亚潮剧文化景观。 潮剧团经泰国或新加坡到英属马来亚作定点演出开始，潮裔移民将 原乡情怀寄托在民俗信仰中逢神诞喜庆时扮演着祭祀仪式功能的潮剧。 因此马来西亚槟城潮剧的发展与庙宇有着莫大的关联，各种时令性的神 庆演出收入是潮剧团主要的经济来源，滋养了本土潮剧团。槟城州因政 经及人口结构因素，开埠后随着潮裔社群经济增强，民间信仰活动主要 是潮剧团的活动区域。槟城潮剧团体历经游艺场、街戏、为望族民家庆 生助兴的演出形式沿革，已然成了当地潮人社会的部分生活内容。本文 从各面向剖析，以现存于槟城潮剧市场的潮剧团实例进行细部分析，探 讨槟城潮剧市场的营运现况与营生现象。由杨丙金携“老赛永丰潮剧团” 到槟城，衍生了迄今的“金玉楼春潮音剧团”和“潮艺馆”的槟城潮剧 团体，随着时局也辗转经历沉寂、复兴、开启发展契机新局面的历程。 世局的变迁迫使“金玉楼春潮音剧团”调整其组织形式与行政管理 以持续营运，让改革创新却不失传统的槟城潮州木偶戏不至于走向绝路。 善用剧团资源和寻谋更好的潮剧传播策略可提升潮剧市场接受值以延续 潮剧团的营运。潮剧所蕴含的文化及人文精神，是凝聚马来西亚潮人同 根同气的文化合力，对潮人起着融情聚力的作用，因此“潮艺馆”竭力 联合马来西亚各潮裔联合会和官方机构，充分发挥文化人的支持作用， 使槟城潮剧团更具策略性与生命力，获得更好的维持和传承，成为支撑潮人团结的精神支柱并维系与故土根脉相连的纽带。 优化与提升槟城潮剧团体质素才能让其更具延续力，克服本土潮剧 团在传承与断层间所面对的冲击现象。迈入新时代的“潮艺馆”以文艺 团体模式着重青少年观众的培育，努力走进校园，走向青少年，汲汲开 展潮剧教育，让有艺术性和观赏性的潮州传统表演艺术走进社区，营造 潮剧发展的良好氛围，使社会潮剧群众基础更广泛、深入、持久和扎实。In existence for thousands of years, Chinese opera is like a river of culture that permeates the social life of generations of the Chinese people, and the colourful regional culture has recreated dramas with rich local colours that share the unique cultural landscape of Chinese opera. Teochew opera, accompanied by large gongs and drums and Teochew orchestral instruments, spread to Southeast Asian countries in the early 20th century by the ancestors of the Chaoshan region. The development of the Malaysian Teochew opera in Penang has strong linkages with the temples, the Teochew people who immigrated to the south placed their hopes and emotions on the folklore and beliefs on the various traditional sacrifices held in the temple during the celebration of the god's birthday. Teochew opera, which plays the function of folklore and beliefs and cultural rituals of the Teochew people, is part of the folklore festival ceremony of sacrifices. Support from the society has always been the main source of economics for Teochew opera troupe, the income generated from various seasonal ceremonial performances continues to nourish the Penang Teochew opera troupe. From Lao Sai Yong Hong Teochew Opera Troupe to Teochew Puppet and Opera House, the local Teochew opera troupe needs to adjust its organizational and administrative management to sustain and adapt to the changes and evaluation of environment to maintain its operations, so that the Malaysian Teochew opera troupe in Penang, through reform and innovation will not lose its traditional tracts and avoid extinction. Under the changes of the country’s economic situation, the local Teochew opera has adopted the strategy of optimizing its available resources and seeking better dissemination of Teochew opera heritage, it aimed to enhance the market acceptance on the value of the troupe for the continued operation of the troupe. Study finds that the traditional culture and humanistic spirit embedded in Teochew opera is the cultural synergy that unites the Malaysian Teochew people and plays a role in culminating feelings and cohesion for the Teochew people. It is hoped that the federation of ethnic Teochews in Malaysia, the public and official institutions can provide full supportive role in spreading of Teochew opera, which becoming a spiritual pillar supporting the unity and struggle of the Teochew people and maintaining their bonding. Only by improving the quality of local Teochew opera, it can be more sustainable and be able to overcome its crisises and challenges. The development of opera is inseparable from its heritage, the opera is currently entering the new era of literary and art organisation, it aims to focus on the nurturing of young audience in a new model, striving to gain entry into school compound, to expose the youth to the education of Teochew opera, thus create a greater society base and foundation for building a more sustaining and solid Teochew opera.